Association Between Paravertebral Muscle Mass and Improvement in Sagittal Imbalance After Decompression Surgery of Lumbar Spinal Stenosis. Issue 6 (15th March 2022) - Yoshida, Yuichi; Ohya, Junichi; Yasukawa, Taiki; Onishi, Yuki; Kunogi, Junichi; Kawamura, Naohiro
Abstract : To clarify the association between paraspinal muscle and the improvement in sagittal imbalance after decompression surgery, we reviewed patients with lumbar spinal stenosis who had spinal sagittal imbalance. Our results revealed that preoperative larger volume of paravertebral muscles and preoperative lower pelvic incidence-lumbar lordosis were significant associated factors for the improvement in sagittal imbalance. Abstract : Study Design: Retrospective observational study. Objective: This study examined associated factors for the improvement in spinal imbalance following decompression surgery without fusion. Summary of Background Data: Several reports have suggested that decompression surgery without fusion may have a beneficial effect on sagittal balance in patients with lumbar spinal stenosis (LSS) through their postoperative course. However, few reports have examined the association between an improvement in sagittal imbalance and spinal sarcopenia. Methods: We retrospectively reviewed 92 patients with LSS and a preoperative sagittal vertical axis (SVA) more than or equal to 40 mm who underwent decompression surgery without fusion at a single institution between April 2017 and October 2018. Patients' background and radiograph parameters and the status of spinal sarcopenia, defined using the relative cross-sectional area (rCSA) of the paravertebral muscle (PVM) and psoas muscle at the L4 caudal endplate level, were assessed. We divided the patients into two groups: those with a postoperative SVA less than 40 mm (balanced group) and those with a postoperative SVA more than or equal to 40 mm (imbalanced group). We then compared the variables between the two groups. Results: A total of 29 (31.5%) patients obtained an improved sagittal imbalance after decompression surgery. The rCSA-PVM in the balanced group was significantly higher than that in the imbalanced group ( P = 0.042). The preoperative pelvic incidence (PI)-lumbar lordosis (LL) mismatch ( P = 0.048) and the proportion with compression vertebral fracture ( P = 0.028) in the balanced group were significantly lower than those in the imbalanced group. A multivariate logistic regression analysis identified PI-LL less than or equal to 10° and rCSA-PVM more than or equal to 2.5 as significant associated factor for the improvement in spinal imbalance following decompression surgery. Conclusion: A larger volume of paravertebral muscles and a lower PI-LL were associated with an improvement in sagittal balance in patients with LSS who underwent decompression surgery. Level of Evidence: 3